The Community-Based ‘Mandiri Sejahtera’ Waste Bank Model and Its Adaptation in Environmental Education in Schools: a Case Study in Kedungturi Village, Sidoarjo - M Raka siwi, Raka; Devy Siswaningrum (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
This research examines a collaborative model between Bank Sampah Mandiri Sejahtera and early childhood education institutions (PAUD/Kindergarten) in Kedungturi Village, Sidoarjo Regency, as a sustainable solution to address waste problems in East Java. Using a descriptive-analytical qualitative approach, data were collected through document studies, field observations, and in-depth interviews with waste bank managers and educational stakeholders. The research employs the Triple Bottom Line (3P) framework—Planet, People, Profit—to analyze the environmental, social, and economic impacts of the collaboration. Integrating waste management education into the PAUD/Kindergarten curriculum will instill environmentally conscious character from an early age and strengthen community participation. With CSR support, this model has the potential to be replicated as a sustainable community-based waste management strategy to tackle regional waste challenges.